Pelatihan SAP Analytics Cloud dan Pengenalan Canva di SLB Karya Murni Medan - Jepronel Saragih; Ronald Belferik; Evander Banjarnahor (Yayasan Literasi Sains Indonesia, 2025)
This community service activity is a collaborative initiative between Universitas Pelita Harapan and SLB Karya Murni Medan, aimed at enhancing digital literacy and technology skills among deaf students. The program focuses on two main areas: Data Science training using SAP Analytics Cloud (SAC) and digital banner and poster design training using Canva. In the SAC training, participants were introduced to fundamental concepts of data analytics, data modeling, data exploration, information visualization, and key features such as Smart Discovery, Designer Mode, and Data Explorer Mode. A COVID-19 dataset was used as a case study to help students understand basic data analysis processes, including how to build models, run simple machine learning algorithms, and generate interactive dashboards. All materials were designed using visual, demonstrative, and applicative approaches to ensure accessibility for students with special needs and to support a gradual learning process. In addition, the Canva training was provided to foster students’ creativity in creating informative and visually appealing digital banners and posters. The results of the program show that the students were able to create simple data models, understand basic visualizations, and produce digital design works. This program provides a meaningful contribution to the empowerment of inclusive education and strengthens sustainable collaboration between academic institutions and special education schools.